The Role of Self-Employment in Ireland's Older Workforce - Anne Nolan; Alan Barrett (Institute of Labor Economics (IZA), 2018)
A feature of employment at older ages that has been observed in many countries, including Ireland, is the higher share of self-employment among older labour force participants. This pattern of higher self-employment rates at the end of the labour market career may reflect lower rates of retirement among the self-employed compared to employees, as well as transitions into self-employment at older ages. In this paper, we use data from four waves of the Irish Longitudinal Study on Ageing (TILDA), spanning the period 2010-2016, to examine both the characteristics of the older self-employed in Ireland and the determinants of transitions in employment states at older age. We find that the higher proportion of self-employed people at older ages in Ireland results from lower retirement rates among the self-employed and not from transitions from employment to self-employment. This is in contrast to other countries such as the US where transitions into self-employment are more prevalent. We find that the self-employed are older, more likely to be male, and significantly less likely to have any form of supplementary pension cover than the employed. These lower retirement rates and lower degrees of pension cover suggest that standard approaches to pension provision may be less effective in proving attractive to the self-employed in Ireland.
Keywords: D14; H55; J14; J26; 330; retirement; self-employment; older workers; Ireland